The vulgarization of the language of a children’s multiplication text as a psycholinguistic problem - Мамич, Мирослава Володимирівна; Мамич, М. В.; Мамич, Мирослава Владимировна; Mamych, Myroslava V.; Mamich, Miroslava (Hryhorii Skovoroda University in Pereiaslav, 2019)
Research aim is to identify the phenomena of verbal vulgarization of children’s cartoon discourse, to determine their functional-semantic loads and registers of reduced emotional evaluation, as well as the main socio-cultural types of corporate vulgar behavior. Research Methods. The study of the vulgarization of children’s media content was carried out with the help of: a) theoretical methods, b) psycholinguistic empirical methods – discourse-analysis of vulgarized dialogical situations; questionnaire related to the testing of registers of dialogical situations in cinema texts among the audience of student’s youth (80 humanitarian students (specialty «Journalism») of the National University «Odesa Law Academy» aged 17–20 years). Results. The didactic role of animated cinema texts in the formation of media culture is noted. It was proposed the practical analysis of the modern children’s cartoons language in the context of the systematization of markers of affective vulgarity, such as slangisms, jargonisms, elements of common language, obscenisms. On the basis of a survey and psycholinguistic experiment, a stylistic evaluation of the perception of the selected lexical-phraseological material as such that contains the connotation «vulgarity» was confirmed, the attitude of the young generation of viewers to vulgarized cinema text was revealed. Conclusions. Among the main conclusions we may note that as a result of language vulgarization of modern consciousness, in particular children, the so-called conceptual sphere of human activity is changing. The new generation of viewers is focused on low, coarse communication, on the weakening of the feeling of beautiful, on the positive perception of the appropriate aesthetics of everyday life. According to the results of the questionnaire, these cinema texts are perceived neutral by 55 students, positively – 21 students, negatively – 4 students. The language of cartoon characters, which represent certain social groups of real society, is seen as the norm for any situation, and grumpiness, disrespect, psycho-emotional imbalance are seen as their «organic» color. Therefore, the majority, or the vast majority of the respondents, correlated the lexical-phraseological units as jargon that is, acceptable in the youth environment. Modern foreign animation that is presented as translated cinema text, loses the important function of being a mediadidactive source, that is, the medium of producing patterns of individual and collective linguistic behavior.

Мета дослідження – виявити явища вербальної вульгаризації дитячого мультиплікаційного дискурсу, визначити їхнє функціонально-семантичне навантаження і регістри зниженої емоційної оцінки, а також основні соціокультурні типажі корпоративної вульгарної поведінки. Методики дослідження. Вивчення вульгаризації дитячого медіаконтенту здійснено за допомогою: а) теоретичних методів, б) психолінгвістичних емпіричних методів – дискурс-аналізу вульгаризованих діалогічних ситуацій; анкетування, пов’язаного з тестуванням регістрів діалогічних ситуацій у кінотекстах в аудиторії студентської молоді (80 студентів-гуманітаріїв (спеціальність «Журналістика») Національного університету «Одеська юридична академія» віком 17–20 років). Результати. Відзначено дидактичну роль мультиплікаційних кінотекстів у формуванні медіакультури. Запропоновано практичний аналіз мови сучасних дитячих мультиплікаційних фільмів у контексті систематизації маркерів афективної вульгарності – сленгізмів, жаргонізмів, елементів просторіччя, обсценізмів. На основі опитування і психолінгвістичного експерименту підтверджено стилістичну оцінку сприймання виділеного лексикофразеологічного матеріалу як такого, що містить конотацію ‘вульгарність’, виявлено ставлення молодого покоління глядачів до вульгаризованого кінотексту. Висновки. Серед основних висновків застережено, що в результаті вульгаризації мовної свідомості сучасників, зокрема дітей, змінюється так звана концептуальна сфера діяльності людини. Нове покоління глядачів налаштоване на низьке, згрубіле спілкування, на ослаблення відчуття прекрасного, на позитивне сприймання відповідної естетики повсякдення. За результатами анкетування зазначені кінотексти сприймають нейтрально 55 студентів, позитивно – 21 студент, негативно – 4 студенти. Мова персонажів мультфільмів, які представляють певні соціальні прошарки реального суспільства, сприймається як норма для будь-яких ситуацій, а згрубілість, зневажливість, психоемоційна неврівноваженість – як їх «органічне» забарвлення. Тому більшість, або переважна більшість опитуваних співвідносила виділені для стилістичної оцінки лексико-фразеологічні одиниці як жаргонні, тобто прийнятні в молодіжному середовищі. Сучасна іноземна мультиплікація, представлена як перекладений кінотекст, втрачає важливу функцію бути медіадидактичним джерелом, тобто середовищем продукування зразків індивідуальної і колективної мовної поведінки.

Цель исследования – выявить явления вербальной вульгаризации детского мультипликационного дискурса, определить их функционально-семантическую нагрузку и регистры пониженной эмоциональной оценки, а также основные социокультурные типажи корпоративного вульгарного поведения. Методики исследования. Изучение вульгаризации детского медиаконтента осуществлено с помощью: а) теоретических методов, б) психолингвистических эмпирических методов – дискурс-анализа вульгаризированных диалогических ситуаций; анкетирования, связанного с тестированием регистров диалогических ситуаций в кинотекстах в аудитории студенческой молодежи (80 студентов-гуманитариев (специальность «Журналистика») Национального университета «Одесская юридическая академия» в возрасте 17–20 лет). Результаты. Отмечено дидактическую роль мультипликационных кинотекстов в формировании медиакультуры. Предложено практический анализ языка современных детских мультипликационных фильмов в контексте систематизации маркеров аффективной вульгаризации – сленгизмов, жаргонизмов, элементов просторечия, обсценизмов. На основе опроса и психолингвистического эксперимента подтверждено стилистическую оценку восприятия выделенного лексико-фразеологического материала как содержащего коннотацию «вульгарность», выявлено отношение молодого поколения зрителей к вульгаризированному кинотексту. Выводы. Среди основных выводов оговорено, что в результате вульгаризации языкового сознания современников, в частности детей, меняется так называемая концептуальная сфера деятельности человека. Новое поколение зрителей настроено на низкое, грубое общение, на ослабление чувства прекрасного, на положительное восприятие соответствующей эстетики повседневности. По результатам анкетирования указанные кинотексты воспринимают нейтрально 55 студентов, положительно – 21 студент, отрицательно – 4 студента. Язык персонажей мультфильмов, которые представляют определенные социальные слои реального общества, воспринимается как норма для любых ситуаций, а грубость, пренебрежительность, психоэмоциональная неуравновешенность – как их «органическуе» окраску. Поэтому подавляющее большинство опрошенных соотносила выделенные для стилистической оценки лексико-фразеологические единицы как жаргонные, то есть приемлемые в молодежной среде. Современная иностранная мультипликация, представленная как переведенный кинотекст, теряет важную функцию быть медиадидактичним источником, то есть средой продуцирования образцов индивидуального и коллективного речевого поведения.
Вульгаризація мови дитячого мультиплікаційного тексту як психолінгвістична проблема
Mamich M. The vulgarization of the language of a children’s multiplication text as a psycholinguistic problem / M. Mamich // Psycholinguistics. - Vol. 26. - № 2. - Hryhorii Skovoroda University in Pereiaslav, 2019. - P. 260-277.
Keywords: cartoon discourse; speech of a children appose; multiplication film; children’s media content; vulgarism; slangism; obsceneism; linguistic consciousness; adaptive potential of a person; stress tolerance; мова дитячого мультиплікаційного фільму; вульгаризм; сленгізм; обсценізм; мовна свідомість; адаптаційний потенціал особистості; стресостійкість; мультипликационный дискурс; речь детского мультипликационного фильма; детский медиаконтент; вульгаризм; сленгизм; обсценизм; языковое сознание; адаптационный потенциал личности; стрессоустойчивость; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics